1997
DOI: 10.2307/2998172
|View full text |Cite
|
Sign up to set email alerts
|

Uncontested Seats and Electoral Competition for the U.S. House of Representatives Over Time

Abstract: We examine how changes in the incidence of uncontested seats for the U.S. House of Representatives over time reflect responses to partisan change, changes in electoral rules, and long-term secular changes in the American political system. We use a multiple interrupted times series model to test the relationship between the number of uncontested House seats from 1912 to 1994 and the 1932 realignment, midterm elections, the rise of the Republican South, redistricting, the abolition of crossfiling laws in Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…I furthermore examine differences between elections. Following congressional findings that competition is lower in nonpresidential years when there is reduced political interest (Wrighton and Squire 1997), statistical analyses control for whether an election occurred in the midterm (e.g., 2006 or 2010) or the off-year (e.g., 2007 or 2009). 9 Prior work also finds legislative competition is greater immediately after redistricting (Pritchard 1992) or in non-Southern elections (Squire 1989).…”
Section: Empirical Analysesmentioning
confidence: 99%
“…I furthermore examine differences between elections. Following congressional findings that competition is lower in nonpresidential years when there is reduced political interest (Wrighton and Squire 1997), statistical analyses control for whether an election occurred in the midterm (e.g., 2006 or 2010) or the off-year (e.g., 2007 or 2009). 9 Prior work also finds legislative competition is greater immediately after redistricting (Pritchard 1992) or in non-Southern elections (Squire 1989).…”
Section: Empirical Analysesmentioning
confidence: 99%
“…Jacobson and Kernell (1983) and Jacobson (1989) have shown that the incumbent's previous margin of victory and the political preferences of the district influence a potential challenger's decision calculus. The decision by an incumbent to forgo an additional term is another issue of consequence for potential candidates as evidence suggests that experienced candidates are more likely to emerge in open seats, especially in an election following a redistricting cycle (Bianco 1984;Banks and Kiewiet 1989;Carson 2005;Gaddie and Bullock 2000;Hetherington, Larson, and Globetti 2003;Wrighton and Squire 1997). Jacobson (2009) also demonstrates that how much money candidates can raise and spend relative to their opponents can influence candidate emergence decisions.…”
Section: Theories Of Candidate Competition In Congressional Electionsmentioning
confidence: 99%
“…Legislative redistricting might affect the uncontested seat rate by influencing the supply of candidates to run. By disrupting the relationship between incumbents and districts, the decennial redistricting cycle itself does appear to increase the uncontested rate in Congress (Wrighton & Squire, 1997). However, Masket et al (2012) find little evidence that specific redistricting methods affected whether a district was contested in the 2002 state legislative elections.…”
Section: Hypothesesmentioning
confidence: 99%